Programmed Death Ligand 1 Expression and Related Markers in Pleuropulmonary Blastoma. (November 2021) - Alipour, Zahra; Schultz, Kris Ann P; Chen, Ling; Harris, Anne K; Gonzalez, Ivan A; Pfeifer, John; Hill, D Ashley; He, Mai; Dehner, Louis P
Introduction: Pleuropulmonary blastoma (PPB), a rare childhood neoplasm of the lung, is linked to pathogenic DICER1 variants. We investigated checkpoint inhibitor markers including Programmed Death Ligand 1 (PD-L1), PD1, CD8 and tumor mutational burden (TMB) in PPB. Material and Methods: Cases were collected from departmental archives and the International PPB/ DICER1 Registry. Immunohistochemistry (IHC) for PD-L1, PD-1, CD8 and DNA mismatch repair (MMR) genes were performed. In addition, normal-tumor paired whole exome sequencing (WES) was performed in two cases. Results: Twenty-five PPB cases were studied, consisting of Type I (n = 8, including 2 Ir), Type II (n = 8) and Type III (n = 9). PD-L1 combined positive score (CPS) of 1, 4 and 80 was seen in three (3/25, 12.0%) cases of Type II PPB with negative staining in the remaining cases. PD-1 and CD8 stains demonstrated positive correlation ( P < .05). The density of PD1 and CD8 in the interface area was higher than within tumor ( P < .05). The MMR proteins were retained. TMB was 0.65 mutations/Mb in type II PPB with high expression of PD-L1, and 0.94 mutations/Mb in one negative PD-L1 case with metastatic tumor. Conclusion: A small subpopulation of PPB patient might benefit from checkpoint immunotherapy due to positive PD-L1 staining.